2013
DOI: 10.1148/radiol.13121730
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Lobular Hyperplasia and Lobular Carcinoma in Situ at Core Breast Biopsy: Use of Careful Radiologic-Pathologic Correlation to Recommend Excision or Observation

Abstract: When careful radiologic-pathologic correlation is performed and concordance is achieved, women with ALH or LCIS at core biopsy can be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…While pathologic-radiographic concordance is likely more important than pure BIRADS classification, studies reporting both have consistently reported the lowest upgrade rates. Atkins et al 23 reported no upgrades among 38 concordant lesions, Chaudhary et al 25 reported an upgrade rate of 3% among 87 concordant lesions, and, similar to our study, Murray et al 32 conducted a prospective study of 80 excisions following a core biopsy diagnosis of pure LN and reported 2 upgrades (3%) among 72 concordant cases. In contrast, in the discordant group, the upgrade rate was 3/8 (38%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While pathologic-radiographic concordance is likely more important than pure BIRADS classification, studies reporting both have consistently reported the lowest upgrade rates. Atkins et al 23 reported no upgrades among 38 concordant lesions, Chaudhary et al 25 reported an upgrade rate of 3% among 87 concordant lesions, and, similar to our study, Murray et al 32 conducted a prospective study of 80 excisions following a core biopsy diagnosis of pure LN and reported 2 upgrades (3%) among 72 concordant cases. In contrast, in the discordant group, the upgrade rate was 3/8 (38%).…”
Section: Discussionsupporting
confidence: 88%
“…Table 4 7,14,1921,2331 summarizes the findings of the more contemporary, larger (comprising more than 20 cases) series on this subject and demonstrates that upgrade rates remain highly variable, ranging from 0% to 27%. In our prospective study with strict eligibility criteria and central pathology review, we found an upgrade rate for concordant, BI-RADS 4 or lower, pure LN lesions to be 3% based on the local pathology diagnosis and 1% based on central pathology review.…”
Section: Discussionmentioning
confidence: 96%
“…Studies seek to find parameters that facilitate the management of patients diagnosed with precursor lesions on percutaneous biopsy, informing decisions regarding the choice between surgery and follow-up alone. A multidisciplinary team can offer individualized treatment options for patients with concordant findings in the imaging and histological analyses ( 32 - 34 ) . Precursor lesions are of low grade, with a low risk for disease progression ( 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, women with high-risk proliferative breast lesions (atypical hyperplasia [ALH], or LCIS) on needle biopsy have been referred for surgical excision due to the possibility of a co-existing, occult carcinoma at the site of the residual imaging abnormality (1822). While this topic remains controversial, recent reports suggest that not all women with ALH or LCIS on needle biopsy require surgical excision to rule out a higher grade lesion (2328).…”
Section: Histopathologic Considerationsmentioning
confidence: 99%